2021
DOI: 10.3389/fmicb.2021.782934
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Gaseous Interventions for Listeria monocytogenes Control in Fresh Apple Cold Storage

Abstract: Listeria monocytogenes (L. monocytogenes) causes an estimated 1600 foodborne illnesses and 260 deaths annually in the U.S. These outbreaks are a major concern for the apple industry since fresh produce cannot be treated with thermal technologies for pathogen control before human consumption. Recent caramel apple outbreaks indicate that the current non-thermal sanitizing protocol may not be sufficient for pathogen decontamination. Federal regulations provide guidance to apple processors on sanitizer residue lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It is important to note that ClO 2 did not induce upregulation of hly and clpC expression on apple waxed surfaces, which may provide protection from fumigation chemicals by absorbing oxidative stress through slight lipid peroxidation. reduction for 1 month (Guan et al, 2021;Guan et al, 2023). In addition, there was no significant impact on the quality or antioxidant values of apples fumigated with ClO 2 (Guan et al, 2021(Guan et al, , 2023.…”
Section: Gene Expression Of Hly and Clpcmentioning
confidence: 87%
See 3 more Smart Citations
“…It is important to note that ClO 2 did not induce upregulation of hly and clpC expression on apple waxed surfaces, which may provide protection from fumigation chemicals by absorbing oxidative stress through slight lipid peroxidation. reduction for 1 month (Guan et al, 2021;Guan et al, 2023). In addition, there was no significant impact on the quality or antioxidant values of apples fumigated with ClO 2 (Guan et al, 2021(Guan et al, , 2023.…”
Section: Gene Expression Of Hly and Clpcmentioning
confidence: 87%
“…Listeria monocytogenes ( L. monocytogenes ) is a gram‐positive, facultatively anaerobic, non‐spore‐forming, and intracellular foodborne pathogen that causes listeriosis (Guan et al, 2021). The Centers for Disease Control and Prevention (CDC, 2021) reports that Listeria outbreaks are associated with an estimated 1600 cases of listeriosis and 260 deaths annually in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic compounds are widely recognized as the primary compounds involved in the overall antioxidant capacity of fruits and vegetables. Cutting or damaging fruit triggers a cellular response that activates phenolic biosynthesis, enhancing the nutritional value and health-promoting properties [50][51][52]. Different studies have demonstrated a significant TPC increase and antioxidant activity following wounding in several fresh-cut fruits and vegetables [53][54][55][56][57][58][59].…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%